The Handmaid's Tale: Using Literature and Online Journaling to Facilitate a Self-Study of Feminist Identity in an International Research Collective. Issue 3 (2nd September 2019) - Makaiau, Amber Strong; Ragoonaden, Karen; Leng, Lu; Mangram, Charmaine; Toyoda, Mitsuyo
ABSTRACT: This article explores how five international colleagues from the USA, Canada, China, and Japan use self-study methodologies and online journaling to systematically examine the tensions surrounding the lived experiences of feminist academics in diverse global contexts. It draws from the theoretical foundations of critical qualitative inquiry, self-study, feminist epistemologies, and fiction as research. The main research questions guiding the study are: what is the role of self-study and journaling in an international research collective?, how can contemporary literature inform a self-study about the intersection of gender and career?, and in what ways does journaling with international partners support personal and professional development of multicultural teacher educators?. For 6 months, the authors explored these questions with one another in an interactive online journal. Collaborative analysis of the journal entries produced three major themes: fiction as self-study, scholarship as hope, and scholarship as freedom. The article concludes with the authors' personal views on the importance of online journaling and self-study among educational researchers who are interested in finding tools and structures for navigating the contemporary women's movement within academia.